UP Sigma Beta Sorority UP Mindanao Chapter an integrated image-building campaign plan - Babela, Haila Shasta d. T.
This study focuses on designing an integrated image-building campaign plan for the UP Sigma Beta Sorority UP Mindanao Chapter. The organizational image of the sorority is being the summation of beauty guided by its three(30 thrusts: academic excellence, social involvement, and political leadership. The aim of this study is to strengthen the organizational image of the UP Sigma Beta Sorority UP Mindanao Chapter. It specifically aims to increase the UP Mindanao students? awareness of the sorority?s organizational image and participation in the sorority?s activities and/or events. It also aims strengthen the coherence between the sorority?s intended and perceived image. Market researchers of the sorority?s activities and events, other existing sororities? activities and events, perceptions of the UP Mindanao students and alumnae members of the sorority on the UP Sigma Beta Sorority UP Mindanao Chapter were done. The scope is limited to the academic year 2012 to 2013. Survey questionnaires were used for the data gathering. The logical framework approach was used for analysis. The participation analysis and SWOT Analysis were particularly used. Moreover, the proponent made use of the Integrated Marketing Communication (IMC) Model. The model served as a guide for the overall design of the campaign plan. The marketing communication tools used are public relations efforts, sponsorships, social media, and posters. There are limited to a budget plan of fifty thousand pesos (P/50,000) and a timeframe of one(1) academic year. In conclusion, the campaign plan will benefit the UP Sigma Beta Sorority UP Mindanao Chapter in reestablishing itself to the UP Mindanao students. The evaluation tools provided will measure its effectiveness and success.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication